Prediction of flood peak-discharges in the Raman Watershed, North Raman, Central Lampung - Rossi Farli; Musa Sabariah; Mera Mas; Kastamto; Susarman; Februarman (E3S Web of Conferences)
The Raman Watershed which is located in Pekalongan District covers an area of approximately 4,375 hectares of technically irrigated rice-field. The area was repeatedly hit by extreme flooding during the rainy season. The largest recorded flood occurred in December 2021, with an average daily maximum rainfall of 153 mm. This flood caused serious damage to the primary canal of the North-Raman Irrigation- Area. This research objective is to predict the flood peak-discharge in the Raman Watershed in the rainy season in December 2021. Flood discharge is calculated for various return periods based on daily rainfall- data from 2012 to 2021 obtained from BMKG Central Lampung. Hydrological analysis includes: 1) assessment of annual average rainfall-depth using the Thiessen method; 2) analysis of rainfall distribution and predictions of design rainfall using three common probability distributions; and 3) flood discharges are predicted using the Nakayasu method. Distribution analysis shows that LPT3 is the most suitable distribution. The average daily maximum rainfall recorded in December 2021 (153 mm), is in very good agreement with the design rainfall for the 25-year return period (152.58 mm). Thus, the flood peak-discharge in the Raman Watershed with average daily maximum rainfall of 153 mm is estimated at 23.27 m3/s.